Regularized immersed boundary-type formulation for fast transient dynamics with fluid-structure interaction. (June 2017) - Jamond, Olivier; Faucher, Vincent
Highlights: A new formulation for immersed boundary-type fluid structure links is proposed. It is based on a regularized expression of the work on the fluid-structure interface. It requires specific geometric software elements to compute the link coefficients. It efficiently prevents the appearance of artifacts in the fluid pressure forces. Abstract: The present article deals with fast transient phenomena involving fluids and structures undergoing large displacements and rotations, associated with non-linear local behavior, such as plasticity, damage and failure. In this context, classical Arbitrary Lagrangian Eulerian approaches reach a limit where it is not possible to update the fluid grid to follow the structural motion without encountering entangled fluid cells forcing the simulations to stop. So-called immersed boundary approaches are thus frequently preferred in this situation, since they allow breaking the topological connection between the fluid and structural meshes and retrieve the expected level of robustness to handle complex structural motions. Their potential for efficient, robust and accurate simulations at the industrial level has been proven. However, it appears that the classical implementation of such approaches still imposes some constraints over the fluid mesh with respect to the structural mesh in terms of cell sizes, due to the expression of the kinematic links between fluid and structural velocities, which must be improved. It is demonstrated in the present article that an extended regularized framework can be designed to overcome the current drawbacks, but it comes with a significant increase of computational complexity and requires an extension of the classical software features encountered in fast transient dynamics simulation programs.